Fahr's disease: an incidental finding in a patient of tubercular meningitis. (3rd December 2012) - Aggarwal, Puneet; Kumar, Gunjan; Dev, Nishanth; Jain, Shalabh
Abstract : Fahr's disease, also known as idiopathic basal ganglia calcification, is a rare clinical entity characterised by bilaterally symmetric calcification of the basal ganglia. Most of the patients present with extrapyramidal symptoms, but the natural history, progression and treatment still remain unknown. We report a case of tubercular meningitis diagnosed by a cerebrospinal fluid examination with incidental findings of an extensive basal ganglia calcification on CT. CT of sibling, done to evaluate an episode of seizure, revealed strikingly similar calcification. Both these calcifications were due to Fahr's disease. The patient was treated with antitubercular and antiepileptic drugs. The patient fully recovered clinically and currently is seizure-free on antiepileptic treatment.